1975
DOI: 10.1159/000175610
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin B<sub>6</sub> on Leucine-Induced Metabolic Changes

Abstract: Administration of leucine at 3 % level in the diet has been shown to increase tryptophan oxygenase activity and to decrease kynureninase activity in the liver and to increase quinolinic acid excretion in the urine of rats fed low amounts of vitamin B6 (0.5 µg/g diet). Vitamin B6 at 3 µg/g of diet was able to reverse the effects of leucine on enzyme activities, but not on quinolinic acid excretion. Isoleucine at 0.2 % level could counteract the leucine effect on kynureninase but not on try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…2 (2) We also showed in rats on marginal intakes of pyridoxine, that leucine further aggravated vitamin B6 deficiency as judged by a low-ered kynureninase, a vitamin B6 dependent enzyme. 3 (3) Our group also demonstrated that the decreased activity of enzyme QPRT brought about by leucine feeding is counteracted by higher amounts of vitamin B6 in the diet.4 (4) Leucine amino transferase, an enzyme which is also pyridoxine-dependent was shown to be stimulated both by leucine as well as by higher amounts of vitamin B6 in the diet5 (5) Tryptophan load test in pellagrins indicated vitamin B6 deficiency.6 Our preliminary clinical trials and leucine tolerance studies also indicate that vitamin B6 administration can effectively cure pellagra and also improve leucine tolerance.…”
Section: Effect Of Excess Leucine On Tryptophan Niacin Pathway and Pymentioning
confidence: 99%
“…2 (2) We also showed in rats on marginal intakes of pyridoxine, that leucine further aggravated vitamin B6 deficiency as judged by a low-ered kynureninase, a vitamin B6 dependent enzyme. 3 (3) Our group also demonstrated that the decreased activity of enzyme QPRT brought about by leucine feeding is counteracted by higher amounts of vitamin B6 in the diet.4 (4) Leucine amino transferase, an enzyme which is also pyridoxine-dependent was shown to be stimulated both by leucine as well as by higher amounts of vitamin B6 in the diet5 (5) Tryptophan load test in pellagrins indicated vitamin B6 deficiency.6 Our preliminary clinical trials and leucine tolerance studies also indicate that vitamin B6 administration can effectively cure pellagra and also improve leucine tolerance.…”
Section: Effect Of Excess Leucine On Tryptophan Niacin Pathway and Pymentioning
confidence: 99%
“…With excess dietary leucine the levels of tryptophan oxygenase and picolinate carboxylase are increased, whereas qui nolinic phosphoribosyl transferase activity is decreased [Ghafoorunissa and Rao, 1973;Rao et al, 1975]. Dietary leucine is also known to induce leucine aminotransferase [Krishnaswami and Rao, 1978].…”
Section: Introductionmentioning
confidence: 99%